1995
DOI: 10.1007/bf00919594
|View full text |Cite
|
Sign up to set email alerts
|

Cold: A risk factor for stroke?

Abstract: A retrospective study was performed to investigate seasonal variation in stroke incidence and to evaluate the hypothesis that cold might be a risk factor. Data were obtained from the central registry of the Hospital de S. João, Porto, Portugal, concerning 4048 patients consecutively admitted for cerebrovascular disease during a period of 33 months. Monthly admissions for stroke and its subtypes were related to mean values of ambient temperature using linear correlation. There was a strong inverse correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 17 publications
9
34
0
5
Order By: Relevance
“…Other prior studies have also reported that higher air pollution levels and greater levels of depression can lead to a correspondingly higher prevalence of strokes. [31][32][33][34][35][36][37] Furthermore, it is also possible that those study subjects in the upper income group would be more likely to reside in the less urbanized areas and more likely to receive regular health check-ups, possibly from private health care facilities which tend to be better equipped; thus, they would be at a lower risk of suffering a stroke attack. In contrast, the study subjects in the lower income group may well work and live in the inner city areas, and for various reasons, may be exposed to a higher risk of disease and a corresponding increase in the risk of a stroke attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prior studies have also reported that higher air pollution levels and greater levels of depression can lead to a correspondingly higher prevalence of strokes. [31][32][33][34][35][36][37] Furthermore, it is also possible that those study subjects in the upper income group would be more likely to reside in the less urbanized areas and more likely to receive regular health check-ups, possibly from private health care facilities which tend to be better equipped; thus, they would be at a lower risk of suffering a stroke attack. In contrast, the study subjects in the lower income group may well work and live in the inner city areas, and for various reasons, may be exposed to a higher risk of disease and a corresponding increase in the risk of a stroke attack.…”
Section: Discussionmentioning
confidence: 99%
“…Given that some of the prior literature has consistently demonstrated that fluctuations in climate have a significant impact on the occurrence of strokes, [31][32][33][34] it is possible that the majority of the communities at urbanization level 2 would be located in the central and southern regions of Taiwan, which are renowned for having a very stable climate, and this could potentially affect this result.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies. 2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men. 32) Our data resembled the results of 10 years of the Canadian Collaborative Study Group although the lowest occurrence in their male group was in summer whereas that of in the present study was in winter.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation